Efforts to Handle Lobster Seed Smuggling in West Tanjung Jabung Regency (Law Enforcement Perspective) (International Forum of Researchers and Lecturers, 2025)
Lobster is one of Indonesia's marine resources that has high economic value and is very important for the country's economy, but excessive lobster fishing and smuggling of lobster seeds have caused a decrease in the productivity of marine resources and significant state losses, so effective law enforcement efforts are needed to protect Indonesia's marine resources from these illegal acts. The problem in this study is how the law enforcement by the West Tanjung Jabung Police against the crime of smuggling lobster seeds (Study of Case Register Decision Number: 144 / Pid.Sus / 2023 / Pn Klt), and what factors are the causes. The research method used is normative juridical, a type of legal research that focuses on the analysis and interpretation of legal norms that apply in a legal system. The study shows that the three defendants in the crime of smuggling lobster seeds were sentenced to 2 years in prison and a fine of IDR 5,000,000 based on Article 27 number 26 Article 92 of Law Number 6 of 2023 concerning Job Creation. The factors causing this crime include internal factors (economic and education) and external factors (politics, environment, and lack of security). Suggestions from the study are: Reviewing the lobster seed export policy. Improving coordination between law enforcement officers and community participation. Improving the capacity and competence of law enforcement personnel.